Caracterização das respostas evocadas auditivas em regime permanente no mesencéfalo de ratos Wistar - Gustavo Coelho Lopes (2011)
Tonotopic bands along the basilar membrane within the cochlea, function as a system of spectral decomposition of the sound stimulus . Thus, the cochlear sensory neurons are responding to a characteristic frequency of sound stimulation and its activity depends on the intensity of the stimulus. The response to the sound ascends to the cortex by auditory pathways, generating along the way, electrical activity that makes part of the Auditory Evoked Potentials (AEPs). The AEPs are an important diagnostic tool and, lately, has been used in applications that go beyond the scope of the assessment of hearing. We can divide the AEPs didactically into two major groups according to the frequency of stimuli: Transient Evoked Potentials and Auditory Steady State Responses (ASSR). The ASSR use an auditory stimulus more physiological and allows a more rapid assessment of the integrity of auditory pathways in addition, however, the biological aspects of REAP are much less studied than the AEPs. In this work we mapped the ASSR in the midbrain of Wistar rats (monopolar electrodes implanted deep) by an anatomical scanning using different patterns of auditory stimuli.To evaluate a possible application of this method in the tonotopic location of the IC layers, we used amplitude modulated tones. We observed that the intensity of the response is directly proportional to the intensity of the stimulus, this shows that there is an optimal intensity range to record these responses. Moreover, the frequency modulation can vary the peak response according to anatomical position. And modulation frequencies between 70Hz and 120Hz show a greater stability compared to other frequencies. Since then suggested for studies that will use tool such as ASSR quantification of physiological changes. The ability to tonotopic location of sites might be achieved with the use of bipolar electrodes and lower anatomical scanning step